Drug-Induced Acute Kidney Injury: A Standardized Patient Case for Clerkship Students - Rebecca Kramer (Association of American Medical Colleges, 2017)
Introduction Drug-induced nephrotoxicity is a common yet preventable cause of acute renal failure. With the upward trend of prescription and over-the-counter medication use, it has become increasingly important for health care professionals to not only be able to identify acute renal failure precipitated by medications, but also to recognize medications that are eliminated by the kidneys and adjust dosages accordingly to prevent further damage. Methods In this activity, third-year clerkship medical students are presented with a standardized patient portraying an acute medical problem in which students must ascertain the underlying cause of the problem and draw from their knowledge of pharmacology, pharmacokinetic principles, and clinical therapeutics to develop a plan to address the patient's medical concerns. Results We found that few students were able to identify the underlying cause of the patient's acute condition, and none were successful at applying pharmacokinetic principles appropriately. Discussion Implementing this case with third-year medical students has identified the need to revisit pharmacokinetic principles in an applied setting. As a result, this topic is being added to a course that highlights the relevance of basic sciences in clinical contexts for clerkship students.